Republic of Kazakhstan : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper on the Republic of Kazakhstan underlies growth of the non-oil sector, fiscal management of oil wealth, and bank credit growth. The share of tradables in the non-oil sector has declined significantly, both in terms of value added and employment, while many nontradable activities, especially services and construction, have expanded. Kazakhstan can sustain non-oil deficits of more than 5 percent of GDP in the near term without reducing the value of oil wealth. Recent developments in the pattern of bank lending and borrowing have led to increased exposure to the property sector and international financial markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet